Health education needs of the youth - Vehlia de Jong (AOSIS, 1985)
The World Health Organisation has declared that the year 1985 is the International Year of the Youth - youth being defined as the young people in the thirteen to twenty four- year age group. This age group often escapes contact with the medical and nursing professions because of their general good health and therefore minimal need for medical care. However, the youth in South Africa, both Black and White, do have health educational needs that are to a large degree neglected and unmet.